The Effect of Macroprudential Policy on Credit Growth and Financing of MSMEs in Indonesia - Ade Surya Sukma; Sunaryati (EkBis: Jurnal Ekonomi dan Bisnis, 2022)
The global crisis in 2008 had weakened the Financial System Stability (FFS) of almost every country. This financial crisis proved that the country had not been really responsive to global change so the financial system risk management done by the central bank was not able to stabilize the crisis. The formulation of macroprudential policies aims to mitigate the bank behavior in distributing credits and financing to the MSMEs which are pro-cyclical. Macroprudential policy instruments used in this study are Loan to Value (LTV)/ Financing to Value (FTV) and Minimum Statutory Reserves based on Loan to Deposit Ratio (LDR)/ Financing to Deposit Ratio (FDR). In addition, there are also macroeconomic variables and bank liquidity variables. The purpose of this study is to see how the influence of macroprudential policies on credit growth and MSME financing distributed by banks. The research method used is the Vector Error Correction Model (VECM) analysis using time series data from January 2010 to July 2020. The results show that macroprudential policies have not been able to suppress financing and in general the macroeconomic variables and bank liquidity also have an influence on credit and financing.